2021
DOI: 10.1186/s12890-021-01763-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting acute respiratory distress syndrome in influenza pneumonia patients using delta mean platelet volume

Abstract: Background Patients with influenza pneumonia are at high risk of rapid progression to acute respiratory distress syndrome (ARDS). Mean platelet volume (MPV), which reflects platelet size, is considered to be a crucial inflammatory marker. The study aim was to investigate the role of delta mean platelet volume (delta MPV) in predicting ARDS in patients with influenza pneumonia. Methods This retrospective study was conducted in a tertiary care centre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…But influenza B was not included in the study population. It also demonstrated high white cell count, thrombocytosis, low mean platelet volume in lower respiratory tract infections by adeno virus in the same category [ 17 ] Serial increase in mean platelet volume (δ) estimation was used to predict the progression to pneumonia in children and ARDS in adults during Influenza pandemics in Thailand study by Teeraphat et al [ 18 ]. It has been identified that platelets engulf viral particles of Influenza which bind to platelet sialoglycans resulting in the removal of sialic acid by viral neuraminidase.…”
Section: Discussionmentioning
confidence: 99%
“…But influenza B was not included in the study population. It also demonstrated high white cell count, thrombocytosis, low mean platelet volume in lower respiratory tract infections by adeno virus in the same category [ 17 ] Serial increase in mean platelet volume (δ) estimation was used to predict the progression to pneumonia in children and ARDS in adults during Influenza pandemics in Thailand study by Teeraphat et al [ 18 ]. It has been identified that platelets engulf viral particles of Influenza which bind to platelet sialoglycans resulting in the removal of sialic acid by viral neuraminidase.…”
Section: Discussionmentioning
confidence: 99%
“…Among sepsis patients, an increase in mean platelet volume from baseline is associated with mortality in patients with severe sepsis or septic shock [ 8 ]. Among influenza pneumonia patients, the change of MVP strongly predicts acute respiratory distress syndrome [ 9 ]. It was also reported that higher MPV was an independent risk factors for the poor prognosis of patients with acute pulmonary embolism [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mean platelet volume (MPV), a routinely measured marker in clinical practice, is a simple, easy, available, and accurate indicator of platelet size and function [ 11 ]. Numerous studies have demonstrated that MPV levels or the change of MPV were correlated with serious compilation or poor prognosis for ICU patients [ 12 , 13 ], sepsis [ 14 , 15 ], influenza pneumonia [ 16 ], acute pulmonary embolism [ 17 ].In addition, MPV also has been shown to be a valuable prognostic marker for patients following acute abdominal surgery [ 18 ], chronic obstructive pulmonary disease (COPD) patients [ 19 ], coronary artery disease [ 20 ] and Type 2 Diabetes Mellitus [ 21 ].…”
Section: Introductionmentioning
confidence: 99%